Nursing Ethics as a Foundation in Nursing Practice: A Literature Review - Dewi, Ni Made Ratih Comala; Aryana, I Gusti Ngurah; Bela, I Kadek Miki Indra; Widiastuti, Ni Kadek Nefi; Putra, I Kadek Andika Dwi; Satriani, Ni luh Adi (Babali Publisher, 2024)
Introduction: Complexity in the healthcare environment causes problems in nursing practice. The nursing code of ethics has been designed as an appropriate guideline for behavior and helps decision-making. Nursing ethics requires nurses to comply with ethical principles to produce quality nursing care. Therefore, this study aims to illustrate the importance of nursing ethics as a foundation for nursing practice.Methods: In the case of the current research, the articles were selected according to PRISMA guidelines. A literature review used three journal databases: ScienceDirect, PubMed, and Google Scholar. The keywords in this literature review are adjusted to the Medical Subject Heading (MeSH), which consists of